Machiavelli’s Impact on the Modern Leadership Discourse and Alternative Perspectives from Islamic Siyasatnama Tradition Al-Shayzari’s Political Strategies - Semih Ceyhan (Türkiye İslam İktisadı Dergisi)
This study aims for comparing the Western and Islamic roots of leadership in political history. In this respect, it presents a comparative content analysis of the Prince by Machiavelli and Political Strategies by al-Shayzari, a 12th century Muslim scholar. Although there are similarities in some respects, there are still significant differences between their leadership discourses. While Machiavelli places the leaders’ interest as the highest priority, al-Shayzari places greatest importance to societal wellbeing and morality. Modern Western leadership discourse seems to borrow many concepts from Machiavelli, and interprets them with a capitalist perspective, leading to distorted managerial & economic perspectives overemphasizing profit maximization. This so-called “Machiavellian” focus is subject to criticism for undervaluing societal wellbeing. This article provides a comparative study by exploring a historical Islamic treatise which can provide challenging managerial and economic perspectives.